Skewed Normal Distribution Of Return Assets In Call European Option Pricing - Sulistianingsih, Evy (Kreano, Jurnal Matematika Kreatif-Inovatif, 2011)
Option is one of security derivates. In financial market, option is a contract that gives a right (notthe obligation) for its owner to buy or sell a particular asset for a certain price at a certain time.Option can give a guarantee for a risk that can be faced in a market.This paper studies about theuse of Skewed Normal Distribution (SN) in call europeanoption pricing. The SN provides aflexible framework that captures the skewness of log return. We obtain aclosed form solution forthe european call option pricing when log return follow the SN. Then, we will compare optionprices that is obtained by the SN and the Black-Scholes model with the option prices of market.ÃÂ Keywords: skewed normaldistribution, log return, options.